Deaths after police contact in England and Wales: the effects of Article 2 of the European Convention on Human Rights on coronial practice. Issue 2 (22nd June 2016) - Baker, David
Abstract: This paper examines the role of coroners in investigating and reporting on cases of death after police contact (DAPC) in England and Wales. It considers how Article 2 (the right to life) of the European Convention on Human Rights (ECHR) has affected coronial processes and practices. It argues that the effects of Article 2 represent an evolutionary shift in accountability processes surrounding cases of DAPC in England and Wales, but that this shift has in turn been mediated by aspects of institutional structure in the coronial system. It discusses how this shift demonstrates the dynamic relationship between the coronial system, state and society and how this has continued to evolve as a result of external demands.